Pengembangan Multimedia Pembelajaran Interaktif (MPI) Berbasis Canva Pada Mata Pelajaran Rias Wajah Foto Siswa Kecantikan SMKN 1 Pogalan Trenggalek - Elnanda Putri Jayanti; Biyan Yesi Wilujeng; Nieke Andina Wijaya; Sri Dwiyanti (Jurnal Tata Rias, 2025)
Canva-based interactive learning multimedia (MPI) as a learning medium can create learning that is not repetitive, and students will not feel bored during the learning process. The type of research used is research and development (R&D). The data collection methods used were observation, questionnaires, and tests of cognitive and psychomotor learning outcomes. The results showed that (1) The overall average score of media suitability level reviewed from media, material and language was 4.64 points, and the standard was "very feasible"; (2) Statistical analysis of cognitive learning outcomes shows that the learning outcomes of the initial test and the final test have significantly improved with the results of Asymp. Sig. (2 tailed) is 0.000, then the value of sig. < 0.05 indicates acceptance of the hypothesis, while the average psychomotor learning outcomes of 86 > KKTP 80 show completeness overall. (3) The results of the analysis of student responses showed the "very good" category with a percentage of 98%. The results show that Canva-based MPI is excellent for use in learning activities to improve academic achievement and improve student responses to teaching. Keywords: Interactive Learning Multimedia (MPI), Canva, Photo Makeup, R&D